EFFECT OF DISCLOSURE OF INTELLECTUAL CAPITAL AND PROFIT VOLATILITY ON COMPETITIVE ADVANTAGE WITH INTERVENING NET PROFIT MARGIN VARIABLES - Suryati, Adelina; Etty Murwaningsari; Sekar Mayangsari (SEAN Institute, 2022)
This study aims to determine the effect of intellectual capital disclosure on net profit margin, earnings volatility on net profit margin, intellectual capital disclosure on competitive advantage, earnings volatility on competitive advantage and the effect of net profit margin on competitive advantage. The sampling technique used is purposive sampling in banking companies. The data analysis method used in this study used SEM PLS. The results of the research on intellectual capital disclosure have a positive and significant effect on the net profit margin, profit volatility has a negative and significant effect on the net profit margin, the intellectual capital disclosure has a positive and significant effect on competitive advantage and not significant on competitive advantage, earnings volatility has a positive and significant effect on competitive advantage, and net profit margin has a positive and significant effect on competitive advantage.